What determinants of COVID-19 vaccine hesitancy among Chinese nursing students? A cross-sectional study - Wang, Xin; Liu, Ming; Li, Yuanzhen; Mei, Xiaoxiao; Liao, Shuting; Liang, Qingqing; Liu, Yachen (Frontiers in Public Health, 2024)
Background The coronavirus disease 2019 (COVID-19) continues to threaten human health, and health professionals, including nursing students, usually work in healthcare frontiers with a high risk of infection. Vaccination is currently one of the most effective preventive measures. This study aimed to explore the determinants of COVID-19 vaccine hesitancy in nursing students. Methods In November 2022, a sample of undergraduate nursing students was recruited from several medical schools in Anhui Province, China, and an online cross-sectional survey was conducted using the questionnaire star platform (Wenjuanxin). A Chi-square test was used to explore vaccine hesitancy among nursing students with different social demographic characteristics and vaccine attitudes. Binary logistic regression analysis was then used to determine the influence factors of vaccine hesitancy among nursing students. Results A total of 1,090 valid samples were collected in this study. Of these, 27.06% (295) of nursing students reported COVID-19 vaccine hesitancy. The results showed “the need to go out of town recently” (OR = 0.670), “very confident that the outbreak could be controlled sustainably” (OR = 0.393), “feeling at risk of infection” (OR = 0.658), “not being worried/being generally worried about the vaccine's safety” (OR = 0.226 and OR = 0.686, respectively), and “not being worried about the vaccine's effectiveness” (OR = 0.411). These five factors are protective factors associated with COVID-19 vaccine hesitancy in nursing students. The factors “considering the country completely safe from an outbreak” (OR = 3.436), “considering themselves safe because others are vaccinated” (OR = 2.239), and “Agreeing that other protective measures can be relaxed after vaccination with the COVID-19 vaccine” (OR = 2.007) are risk factors associated with COVID-19 vaccine hesitancy among nursing students (P < 0.05). Conclusion Overall, relatively few nursing students had COVID-19 vaccine hesitancy. Schools and relevant institutions still need to actively guide them to improve their confidence in the COVID-19 vaccine, strengthen the prevention and control measures of the epidemic, and improve their awareness of the crisis to improve the vaccination rate to reduce the COVID-19 vaccine hesitancy in nursing students.